Methodology for the Analysis and Assessment of the Reliability of the State and Prediction the Service Life of Reinforced Concrete Structures - A. G. Tamrazian (Железобетонные конструкции)
Reinforced concrete structures can be exposed to aggressive environmental influences, which leads to a decrease in their bearing capacity during their service life. If a safety assessment of such structures is to be carried out in order to be able to continue in service, the main challenge would be to ensure that they can withstand future extreme loads over their intended lifetime with a level of reliability sufficient for safety.There are currently no methodologies for such an assessment.This methodology is proposed to facilitate quantitative assessments of the current and future structural reliability and load-bearing capacity of reinforced concrete structures. This methodology takes into account the random nature of past and future pressures, as well as degradation as a result of negative environmental factors.The time-dependent reliability and deterioration assessment of reinforced concrete structures provides the basis for determining the duration of safe operation.